2009
DOI: 10.1007/s10735-008-9209-7
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 overexpression correlates with tumour progression markers in pancreatic ductal adenocarcinoma

Abstract: The assessment of caveolin-1 (Cav-1) as a marker of tumor aggressiveness in pancreatic ductal adenocarcinoma (PDAC). In this study, we examined the expression of Cav-1 in 34 human PDAC tissue samples and the associated peritumoral tissues by immunohistochemistry and western blot. Additionally, we correlated Cav-1 expression with other tissue (Ki-67, p53) and serum (CA 19-9) tumor markers. In the tumor-derived tissue, both tumor cells and blood vessels expressed Cav-1. In contrast, in peritumoral tissue, Cav-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 31 publications
0
36
1
Order By: Relevance
“…Finally, the authors suggested that positive Cav-1 expression is an independent negative predictor of survival (P=0.0358). In a recent study of 34 pancreatic ductal adenocarcinoma (PDAC) tissue samples, Tanase et al (79) confirmed the prognostic role of the expression of Cav-1. Furthermore, the expression of Cav-1 was found to significantly correlate with Ki-67 and p53, as well as serum levels of CA 19-9.…”
Section: The Role Of Cav-1 Expression In Human Cancer Cellsmentioning
confidence: 90%
See 2 more Smart Citations
“…Finally, the authors suggested that positive Cav-1 expression is an independent negative predictor of survival (P=0.0358). In a recent study of 34 pancreatic ductal adenocarcinoma (PDAC) tissue samples, Tanase et al (79) confirmed the prognostic role of the expression of Cav-1. Furthermore, the expression of Cav-1 was found to significantly correlate with Ki-67 and p53, as well as serum levels of CA 19-9.…”
Section: The Role Of Cav-1 Expression In Human Cancer Cellsmentioning
confidence: 90%
“…Therefore, contradictory roles of Cav-1 expression in human cancer cells have been reported. Certain studies insist that Cav-1 is downregulated and serves as a tumor suppressor in breast cancer (7173), GC (74), hepatic cancer (75) and mucoepidermoid carcinoma (MEC) of the salivary glands (76); while other studies suggest that the expression levels of Cav-1 are upregulated, consistent with advanced tumor stage, high histological type and the metastasis of human cancer cells, including esophagus (77,78), pancreatic (79), renal (80), prostate (81) and colorectal (82) cancer.…”
Section: The Role Of Cav-1 Expression In Human Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research have been performed regarding the local/tissue biomarkers: angiogenic factors [e.g. EGF, VEGF, heparanase, cathepsins (31,32)], matrix metalloproteinase 7, fibroblast activation protein (33), caveolin-1 (34,35) are only a few proteins whose increased expression in pancreatic cancer tissue correlates with an unfavorable prognostic.…”
Section: Angiogenesis and Inflammatory Angiogenesis And Inflammatory mentioning
confidence: 99%
“…However, in peritumoral tissue caveolin-1 is mainly expressed in blood vessels and only occasionally expressed in ductal or parenchymal cells. Overexpression of caveolin-1 is associated with tumor size, grade, stage, and increased serum levels of CA19-9 (Tanase et al, 2009).…”
Section: Relationship Between Caveolin-1 and Pancreatic Cancermentioning
confidence: 99%